Membangun Jiwa Wirausaha Sejak Dini Melalui Pelatihan Pemasaran dan Kewirausahaan Dasar pada Anak Panti Asuhan - Radiva Arjuna; Nurul Komari; Muhammad Yazidul Iman; Dwi Janna’im; Margareta Marta; Frizdha Noor Hanisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Children living in orphanages in Indonesia still face limitations in obtaining life skills education and economic independence development. The lack of entrepreneurship training from an early age makes them socially and economically vulnerable when they enter their productive years. In response to this issue, the Student Work Study Program (KKM) implemented at the Aisyiyah Tunas Harapan Orphanage was designed to provide training in handicrafts and an introduction to basic marketing concepts. Using a Participatory Learning and Action (PLA) approach, the program involved more than 30 participants from diverse educational backgrounds. Activities were conducted in stages through several sessions, including training in making keychains from beads, product packaging techniques, and simple promotional strategies. The results of the activities showed an increase in participants' understanding of marketing concepts, as well as the development of technical skills and entrepreneurial characteristics such as creativity, cooperation, and self-confidence. These findings demonstrate that participatory learning methods based on hands-on practice are effective in fostering entrepreneurial spirit and economic independence among orphanage children. This program also has the potential to serve as a model for community-based economic empowerment that can be applied to other vulnerable groups in society.